Review of uptake of interventions to reduce mother to child transmission of HIV by women aware of their HIV status. Issue 7127 (24th January 1998) - Lyall, E G Hermione; Stainsby, Christopher; Taylor, Graham P; Ait-Khaled, Mounir; Bingham, Samantha; Evans, Jennifer A; Wright, Anne; Weber, Jonathan N; McClure, Myra O; Walters, Sam; Tudor-Williams, Gareth
Abstract: Objectives: To examine the change in uptake of interventions to reduce transmission of HIV from mothers to infants from January 1994 to July 1997. Design: Review of mother-infant pairs who presented for infant diagnosis of HIV infection. Setting: Central London hospital with facilities for diagnosis of infant HIV infection. Subjects: 57 consecutive mother-infant pairs, mainly from central London but also referred from surrounding hospitals. Interventions: Data were collected on mother's country of origin; CD4 count at delivery; plasma HIV RNA copies/ml; mode of delivery; antiretroviral therapy; infant feeding; and HIV infection in infants. Main outcome measures: HIV infection of infants. Results: The vertical transmission rate was 12% (7 pairs; 95% confidence interval 3% to 22%). All mothers chose not to breast feed. The caesarean section rate was 53% (30/57). Antiretroviral therapy was taken by 68.5% (39/57) of mother-infant pairs. With antiretroviral therapy or caesarean section, or both, transmission occurred in 6% (0% to 13%) of pairs (3/50). During the 24 months of 1994 and 1995, 21% (4/19) of infants were infected with HIV; 7.9% (3/38) were infected over the 19 months January 1996 to July 1997. The caesarean section rate did not change over these periods. Use of antiretroviral therapy increased from 31.5% (6/19) to 86.8% (33/38) (P<0.0001). Conclusion: Women with a diagnosis of HIV infection acted to reduce the risk of transmission to their infants. Uptake of antiretroviral therapy increased significantly over time, and the caesarean section rate was persistently high.